Let $|\psi\rangle = \frac{1}{\sqrt{2}}\sum_{k=0}^{1}(-1)^{ka}|k, k \oplus b\rangle $ so that $|\psi'\rangle = \frac{1}{\sqrt{2}}[\sum_{k=2}^{1}(-1)^{ka}(U_{A}|k\rangle \otimes U_{B}|k \oplus b\rangle)]$ where $U_{A}, U_{B}$ are unitary operators.

The action of $U_{A}|k\rangle$ gives $U_{A}|k\rangle = |k_{A}\rangle$ which is equivalent to rotating $|k\rangle$; likewise, $U_{B}|k\rangle = |k_{B} \oplus b_{B}\rangle$.

But correctly: $U_{B}|k\rangle = |k_{B} \oplus b\rangle$.

Why is this so?



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge that you have read and understand our privacy policy and code of conduct.